Osteoporosis, Skin Collagen, and Androgen. Issue 5738 (26th December 1970) - Black, Martin M.; Shuster, Sam; Bottoms, Eva
Abstract : Total skin collagen was found to be decreased in untreated patients with osteoporosis, particularly women, but increased after treatment with androgens in women. Decreased body collagen may possibly be a primary defect in osteoporosis, while androgens may increase total skin collagen.